Dziecko w szkolnej rzeczywistości. Założony a rzeczywisty obraz edukacji elementarnej - Redakcja (Wydawnictwo Naukowe UAM, 2011)
The book presents studies on the present state of pre-school and early school education. The studies were conducted in 2009 in 107 schools in different environments (cities, towns and rural areas) in the whole country. Their aim was to show changes [that have occurred] after 10 years of implementation of reforms in Polish education system. In the book the authors try to answer such questions as: To what extent the school is conducive to a varied and effective child’s activity, to what extent the conception of the holistic perception of a child as an individual subject is comprehended by the teachers, what kinds of teaching techniques and strategies are used by the teachers of young children, what are the achievements in the development of children as far as the main competences and abilities of children who complete their elementary education nowadays? The methods applied, which are based mainly on the study of individual experiences and forms of activity reveal school reality in its many dimensions.
The child in school reality. The assumed and the real picture of elementary education
Keywords: dziecko; child; edukacja elementarna; elementary education; szkolna rzeczywistość; school reality; szkoła; school; badania empiryczne; empirical studies